Neurotecnologie: cenni sulla dimensione biogiuridica dei “neurodiritti” - Luigi Zito (Aequitas Magazine, 2024)
Brief examination of the biolegal dimension of "neurorights" in relation to the increasingly pervasive use of neurotechnologies.